Apakah Produk Beasiswa Bidikmisi dapat Memutus Mata Rantai Kemiskinan di Indonesia? - Rusi Rusmiati Aliyyah; Ahmad Gawdy Prananosa; Ismail Ismail; Endang Sri Budi Herawati; Iman Subasman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the implementation of the product of the Bidik Misi scholarship program. This research uses case study qualitative method. The research was conducted at Djuanda University which is a private university in LLDIKTI region IV. Collecting data using interview instruments, questionnaires, observations, and documentation with data analysis techniques through data reduction, data presentation, and verification. The research findings show that the final results of the Bidik Misi scholarship are in accordance with the program objectives, namely increasing student motivation and achievement, increasing student achievement in the curricular, co-curricular and extracurricular fields, causing an impact for students and prospective students to always improve achievement and be competitive, and produce graduates who are independent, productive and have social concerns to break the chain of poverty and empower the community. Meanwhile, aspects of increasing access and learning opportunities in higher education, as well as ensuring the continuity of student studies to completion and on time, still need improvement. In conclusion, the Bidikmisi scholarship program has produced graduates who are independent, productive and have social awareness, so that they are able to play a role in efforts to break the poverty chain and empower people in Indonesia. Keywords: Outstanding Student, Bidikmisi Scholarship, Higher Education